Eficiência do extrato de alho na superação da dormência de gemas de videira cv. isabel precoce - Farias, Wagner César de (2019)
A limiting factor in commercial grape production is irregular sprouting. In general, a cold period is necessary to overcome the dormancy state and promote uniform bud sprouting. However, there are management practices which can favor sprouting and make it possible to adjust a cultivar to a climate reality. These practices include water management, ring incision, branch bending and the use of chemicals which act as growth regulators. Today, products that have the same effectiveness as hydrogenated cyanamide in overcoming dormancy, but without harming the farmer's health as well as the environment and low cost, have been constantly sought. Because of this and with the purpose of seeking alternative substances with less environmental impact, garlic extract has promising results in overcoming dormancy of temperate fruit trees. The objective of this research was to evaluate the effects of garlic extract (Allium sativum L.) on the phenology and production components of cv. Isabel Early, in the semiarid conditions of the Potiguar West. Experiment I was carried out at Rafael Fernandes Experimental Farm (Lagoinha) in a randomized complete block design with 5 treatments (T1: control - Dormex® - 5%; T2: garlic extract - 25%; T3: garlic extract - 50 T4: Garlic Extract - 75% and T5: Garlic Extract - 100%) and 5 repetitions. Phenological characteristics (F1 - Pruning-budding; F2 - Budding-flowering; F3 - Flowering-fruiting; F4 - Fruiting-ripening; F5-Harvesting) and the percentage of shoots at 15 days after pruning were evaluated. The use of hydrogenated cyanamide showed greater action in overcoming bud dormancy, as well as in anticipation of budding. Garlic extract was effective in overcoming vine dormancy cv. Isabel Early. The C2 concentration (50% garlic extract) showed results close to the control, especially for sprouting. In experiment II, we evaluated the productive aspects (length and diameter of bunches, length and diameter of berries, average weight of berries, length of berry and diameter of berry) and fruit qualities (firmness, Soluble Solids (° Brix), acidity). Titrable (AT% Tartaric Acid) and the SS / AT ratio), performed at the Post Harvest Laboratory of the Rural Federal University of Semi-Arid. The quality characteristics of cv. Isabel Precoce remained within the quality parameters required by the market, except for SS / AT ratio, which had values below the established market standard.